Detection of Infectious Adenovirus in Cell Culture by mRNA Reverse Transcription-PCR - Ko, Gwangpyo (American Society for Microbiology, 2003)
We have developed and evaluated the reverse transcription (RT)-PCR detection of mRNA in cell culture to assay infectious adenoviruses (Ads) by using Ad type 2 (Ad2) and Ad41 as models. Only infectious Ads are detected because they are the only ones able to produce mRNA during replication in cell culture. Three primer sets for RT-PCR amplification of mRNA were evaluated for their sensitivity and specificity: a conserved region of late mRNA transcript encoding a virion structural hexon protein and detecting a wide range of human Ads and two primer sets targeting a region of an early mRNA transcript that specifically detects either Ad2 and Ad5 or Ad40 and Ad41. The mRNAs of infected A549 and Graham 293 cells were recovered from cell lysates with oligo(dT) at different time periods after infection and treated with RNase-free DNase to remove residual contaminating DNA, and then Ad mRNA was detected by RT-PCR assay. The mRNA of Ad2 was detected as early as 6 h after infection at 10(6) infectious units (IU) per cell culture and after longer incubation times at levels as low as 1 to 2 IU per cell culture. The mRNA of Ad41 was detected as soon as 24 h after infection at 10(6) IU per cell culture and at levels as low as 5 IU per cell culture after longer incubation times. To confirm the detection of only infectious viruses, it was shown that no mRNA was detected from Ad2 and Ad41 inactivated by free chlorine or high doses of collimated, monochromatic (254-nm) UV radiation. Detection of Ad2 mRNA exactly coincided with the presence of virus infectivity detected by cytopathogenic effects in cell cultures, but mRNA detection occurred sooner. These results suggest that mRNA detection by RT-PCR assay in inoculated cell cultures is a very sensitive, specific, and rapid method by which to detect infectious Ads in water and other environmental samples.